A study on differences about the influencing factors of depressive symptoms between medical staff and residents during 2022 city-wide temporary static management period to fighting against COVID-19 pandemic in Shanghai - Zhao, Ying; Tao, Yiran; Bao, Xiwen; Ding, Qiang; Han, Changyan; Luo, Tingkun; Zhang, Weijia; Sun, Jinhua; Shi, Jiali (Frontiers in Public Health, 2023)
Objectives: Our study aimed to identify the latent class of depressive symptoms in the Shanghai population during the city-wide temporary static management period and compare differences in the factors influencing depressive symptoms between medical staff and residents. Methods: An online cross-sectional survey was conducted with 840 participants using questionnaires, including Patient Health Questionnaire-9 (PHQ-9), Generalized Anxiety Disorder-7 (GAD7), Pittsburgh Sleep Quality Index (PSQI), and self-compiled questionnaire (demographic characteristics and internet usage time). Latent class analysis (LCA) was performed based on participants’ depressive symptoms. The latent class subgroups were compared using the chi-square test and t-test. Logistic regression was used in our study to analyze the factors influencing depressive symptoms in the medical staff group and residents group and then compare their differences. Results: Two distinct subgroups were identified based on the LCA: the low-depressive symptoms and the high-depressive symptoms groups. There were significant differences between the two groups (P < 0.05) on age, education level, marital status, internet usage time, identity characteristics (medical staff or residents), family income level, living style, overall quality of sleep, and anxiety levels. Furthermore, logistic regression analysis results showed that those with increased internet usage time and daytime dysfunction were nearly twice as likely to experience severe depressive symptoms in the medical staff group than in the residents group. Conclusions: There are differences in the factors influencing depression symptoms between medical staff and residents during the 2022 city-wide temporary static management period to fighting against the COVID-19 pandemic in Shanghai. We should pay special attention to those with increased internet usage time and daytime dysfunction in medical staff working in a special environment such as the COVID-19 pandemic.